Pengaruh Budaya Organisasi dan Motivasi Kerja terhadap Kinerja Karyawan (Studi Kasus PT. Nikomas Gemilang) - Sucipto, Mahendra; Nuranisa, Siti; Astuti, Sri; Haryadi, Didit (Sahabat Publikasi, 2024)
This research aims to determine the influence of Organizational Culture (X1) and Work Motivation (X2) on Employee Performance (Y) at PT. Nikomas Gemilang. Sampling technique in this research is simple random sampling, the sample in this research consisted of 50 respondents. The data collection method uses a questionnaire and the measuring instrument used is a Likert scale. Using IBM SPSS Statistics 24 software. Partial research results (t test) state that the organizational culture variable has tcount > ttable, namely 1.872 > 1.678 and a significance level of 0.067 < 0.05, meaning that organizational culture has a positive and significant influence on employee performance, variable work motivation has a value of tcount > ttable, namely 4.082 > 1.678 and a significance level of 0.000 < 0.05, meaning that work motivation has a positive and significant effect on employee performance, and the variables of organizational culture and work motivation have a value of fcount > ftable, namely 64.456 > 2.802 and a significance level 0.000 > 0.05 means that organizational culture and work motivation have an influence on performance. positive and significant influence on employee performance simultaneously.